Industrial Manufacturing Applications of Zinc Oxide Nanomaterials: A Comprehensive Study - Md Abdus Subhan; Newton Neogi; Kristi Priya Choudhury (Nanomanufacturing, 2022)
Nanomaterials (NMs) that are created with zinc oxide are very valuable for a wide variety of applications. There is a present interest in ZnO nanoparticles in a wide range of industries. This interest may be attributed to the fact that ZnO NPs have many important features. It will be necessary for ZnO NPs to possess certain qualities in order for them to rapidly find uses in industry and for these applications to have an effect on the expansion of the economy. A large surface area, a large bandgap, photocatalytic property, biosensing, bioimaging, and other qualities are included in this list. In this article, the extraordinary characteristics of ZnO NPs, as well as their novel applications in industrial settings and the challenges that come along with their utilization, will be discussed.